Treatment of chemical-pharmaceutical wastewater in packed bed anaerobic reactors - Nacheva, P M (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
Biological degradation in packed bed anaerobic mesophilic reactors with five different support materials was studied for the treatment of chemical-pharmaceutical wastewater with high COD (23-31 g/L), which contains toxic organic compounds. Experimental up-flow bio-filters were operated at different organic loads for a two-year period. Removals of 80-98% were obtained in the reactors with sand, anthracite and black tezontle, but at relatively low organic loads, less than 3.6 kg m(-3)d(-1). The reactor with granular activated carbon (GAC) had a better performance; efficiencies higher than 95% were obtained at loads up to 17 kg m(-3)d(-1) and higher than 80% with loads up to 26 kg m(-3)d(-1). Second in performance was the reactor with red tezontle which allows COD removals higher than 80% with loads up to 6 kg m(-3)d(-1). The use of GAC as support material allows greater biodegradation rates than the rest of the materials and it makes the process more resistant to organic load increases, inhibition effects and toxicity. Methanogenic activity was inhibited at loads higher than 21.9 kg m(-3)d(-1) in the GAC-reactor and at loads higher than 3.6 kg m(-3)d(-1) in the rest of the reactors. At loads lower than the previously mentioned, high methane production yield was obtained, 0.32-0.35 m3CH4/kg CODremoved